PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI KERJA GURU UNTUK MEWUJUDKAN EFEKTIVITAS PEMBELAJARAN - Mulyani, Mela; Ainissyifa, Hilda; Hadiyanto, Nahdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of teacher competence on teacher work motivation and its impact on learning effectiveness at Garut Islamic School Prima Insani Elementary School. This quantitative study used a survey method involving 52 teachers. Data were collected through questionnaires and analyzed using linear regression. The results showed that teacher competence significantly influenced teacher work motivation, and work motivation significantly influenced learning effectiveness. These findings indicate that increasing teacher competence can directly or indirectly improve learning effectiveness through increased work motivation. The research instrument was a 1–5 Likert scale questionnaire that measured teacher competence, work motivation, and learning effectiveness. The analysis results showed that teacher competence significantly influenced teacher work motivation. Work motivation also significantly influenced learning effectiveness. Thus, work motivation is a mediating variable that links teacher competence with learning effectiveness. This study confirms that increasing teacher competence directly and indirectly impacts the quality of learning.